Direct Coal Oxidation in Modified Solid Oxide Fuel Cells. Issue 4 (11th February 2017) - Deleebeeck, L.; Gil, V.; Ippolito, D.; Campana, R.; Hansen, K. Kammer; Holtappels, P.
Abstract : Hybrid direct carbon fuel cells employ a classical solid oxide fuel cell together with carbon dispersed in a carbonate melt on the anode side. In a European project, the utilization of various coals has been investigated with and without addition of an oxidation catalyst to the carbon-carbonate slurry or anode layer. The nature of the coal affects both open circuit voltage and power output. Highest OCV and power densities were observed for bituminous coal and by adding manganese oxide or praseodymium-doped ceria to the carbon/carbonate mixture. Comparing the carbon black fueled performance of an anode supported (315 μm anodes) and cathode supported cell (15 μm anode) indicates a superior performance of the latter. Using un-catalyzed biomass (charcoal) as fuel results in an OCV of 941 mV and a maximum power density of 78 mW/cm 2 at 755°C similar to the power output of manganese oxide catalyzed bituminous coal (73 mW/cm 2 ).